Physicochemical properties associated with the presence of Burkholderia pseudomallei in small ruminant farm water supplies in Peninsular Malaysia - Musa, Hassan Ismail; Hassan, Latiffah; Shamsuddin, Zulkifli; Panchadcharam, Chandrawathani; Zakaria, Zunita; Abdul Aziz, Saleha (Springer, 2018)
Burkholderia pseudomallei causes melioidosis, a life-threatening infection in both humans and animals. Water is an important reservoir of the bacteria and may serve as a source of environmental contamination leading to infection. B. pseudomallei has an unusual ability to survive in water for a long period. This paper investigates physicochemical properties of water associated with the presence of B. pseudomallei in water supply in small ruminant farms in Peninsular Malaysia. Physicochemical properties of water samples taken from small ruminant farms that included temperature, pH, dissolved oxygen (DO2), optical density (OD), and chemical oxygen demand (COD) were measured after which the samples were cultured for B. pseudomallei. Multivariable logistic regression model revealed that slightly acidic water pH and higher COD level were significantly associated with the likelihood of the B. pseudomallei presence in the water.